Consequences of Implementing Integrated Reporting in Nigeria Using A DOI Approach: Array - Adelowotan, Michael O.; Ini E., Udofia (Acta Universitatis Danubius. Œconomica, 2021)
Research efforts have supported the need for more accountability by organisations to stakeholders about their performance in reaching their long term vision through the use of integrated reporting. This study examined the consequences arising from IR implementation using diffusion of innovation theory approach. The study utilized primary data obtained from a survey of 485 users of corporate reports. The data gathered through a questionnaire was analysed using descriptive statistical tools. Purposive sampling technique was used in selecting the sample for the study. The findings showed that corporate governance, financial performance, corporate attributes and the influence of stakeholders in the external environment have significant influence in the diffusion of IR. These users perceived that the benefits of IR adoption have strong motivation for adoption but there are three major factors militating against this diffusion. These include increased monitoring from regulatory authorities; exposure of confidential information and high cost of implementation. It is recommended that regulators of corporate entities in Nigeria should consider phased implementation of IR across various economic sectors rather than mandatory adoption. Secondly, they should liaise with management of quoted companies before embarking on mandatory IR adoption, by providing needed technical and infrastructural support that would ease some of the challenges arising from IR adoption.